Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1590/s0036-36342012000500003
|View full text |Cite
|
Sign up to set email alerts
|

Compliance to micronutrient supplementation in children 3 to 24 months of age from a semi-rural community in Mexico

Abstract: Compliance to micronutrient supplementation in children 3 to 24 months of age from a semi-rural community in Mexico.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 31 publications
(58 reference statements)
0
9
0
1
Order By: Relevance
“…However, we posit that these pathways are likely to overlap, thus we present a number pathways through which women’s education may impact on child nutrition beyond the effects of income, as proposed in the literature. These pathways indicate that women’s education: Transmits information about maternal and child health and nutrition directly to women, improving mothers awareness and knowledge [ 8 , 32 , 43 47 ] Teaches numeracy and literacy, making the acquisition of information more easily attainable [ 44 , 48 ] Ensures exposure to new environments, increasing receptivity to modern health and nutrition knowledge [ 44 , 49 ] Builds greater self-confidence, enhancing women’s roles in decision making and their interactions with health-care professionals [ 43 , 46 ] (Though some research indicates this pathway was not present [ 50 , 51 ] Provides women with opportunities to form social networks that support women’s empowerment Is a proxy for other socioeconomic factors and intergenerational or household patterns [ 44 , 49 , 52 , 53 ] Delays age of marriage and first child, resulting in fewer and healthier children [ 54 – 56 ] …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we posit that these pathways are likely to overlap, thus we present a number pathways through which women’s education may impact on child nutrition beyond the effects of income, as proposed in the literature. These pathways indicate that women’s education: Transmits information about maternal and child health and nutrition directly to women, improving mothers awareness and knowledge [ 8 , 32 , 43 47 ] Teaches numeracy and literacy, making the acquisition of information more easily attainable [ 44 , 48 ] Ensures exposure to new environments, increasing receptivity to modern health and nutrition knowledge [ 44 , 49 ] Builds greater self-confidence, enhancing women’s roles in decision making and their interactions with health-care professionals [ 43 , 46 ] (Though some research indicates this pathway was not present [ 50 , 51 ] Provides women with opportunities to form social networks that support women’s empowerment Is a proxy for other socioeconomic factors and intergenerational or household patterns [ 44 , 49 , 52 , 53 ] Delays age of marriage and first child, resulting in fewer and healthier children [ 54 – 56 ] …”
Section: Discussionmentioning
confidence: 99%
“…Teaches numeracy and literacy, making the acquisition of information more easily attainable [ 44 , 48 ]…”
Section: Discussionmentioning
confidence: 99%
“…Side effects have traditionally been a concern with other iron supplements as reflected by studies on pregnant women [ 28 , 33 , 34 ] where adherence was negatively influenced. Nevertheless, there are also studies that concluded the other way round [ 35 , 36 ]. In case of MMNP, studies from Bangladesh [ 13 , 25 ] have reported change in color and consistency of stool as common side effects in children.…”
Section: Discussionmentioning
confidence: 99%
“…An exact definition of "compliance" to iron supplementation is lacking in the literature. A study from Mexico calculated adequate compliance by using the number of days the supplement was consumed and the field staff visited to administer the syrup 27 . We could not use this method because we questioned parents retrospectively.…”
Section: Discussionmentioning
confidence: 99%
“…28 Comparison of three groups revealed multiparity and less maternal education as additional risk factors of IDA. Lopez-Florez et al 27 have drawn attention to lower maternal education as a risk factor for incompliance to iron in infants. We believe that multiparity may also increase risk of IDA of infants as it's linked with maternal anemia.…”
Section: Discussionmentioning
confidence: 99%